2022
DOI: 10.1186/s41182-022-00424-5
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of use and choice of modern contraceptive methods in Ghana

Abstract: Background The slow pace of fertility decline in Africa relative to other parts of the world has important implications for the region’s economic development. Modern contraceptive use is seen as important population control and family planning strategy by governments worldwide. This paper examines the socioeconomic determinants of modern contraceptive use and choice among Ghanaian men and women. Methods We use the most recent and nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Enormous studies done in sub-Saharan Africa have found a strong positive effect of wealth index on mFP use [29][30][31][32][33][34][35][36]. Such findings show how financial constraint could have role in reducing mFP usage among poor women.…”
Section: Discussionmentioning
confidence: 76%
“…Enormous studies done in sub-Saharan Africa have found a strong positive effect of wealth index on mFP use [29][30][31][32][33][34][35][36]. Such findings show how financial constraint could have role in reducing mFP usage among poor women.…”
Section: Discussionmentioning
confidence: 76%
“…The decision to use contraception is influenced by a complex interplay of factors involving women and their partners, including individual-level factors (such as women's age, education, and employment) and household-level factors (such as partner's education, occupation, number of children ever born, and wealth quintile) [9][10][11][12][13][14][15][16][17][18]. Community-(such as place of residence and region) and healthcare facility-level factors (such as the availability of contraceptives at the healthcare facility) and cultural factors can also influence this decision [9][10][11][12][13][14][15][16][17][18][19]. For example, in societies with a strong cultural preference for male children, couples with only daughters are less likely to use contraception than those with at least one son [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low uptake of modern contraceptives (20%) in rural areas in Ethiopia was linked to high fertility rates, unintended pregnancies, and unsafe abortions, all of which increase maternal morbidity and mortality [4]. In Ghana, where equitable access to safe and effective contraceptive methods is considered a fundamental human right, low utilization of modern contraceptives was shown to be associated with elevated rates of fertility, maternal and infant mortality, and poverty [19].…”
Section: Introductionmentioning
confidence: 99%